Malignancy and Mortality in Idiopathic Inflammatory Myositis: A Retrospective Single-Center Cohort Study - Ulutaş, Firdevs; Çobankara, Veli (The European Research Journal, 2026)
Objective: Idiopathic inflammatory myositis (IIMs) comprise a heterogeneous group of rare autoimmune muscle diseases characterized by variable clinical presentations and outcomes. While infections are a common cause of early mortality, malignancy has been recognized as the predominant driver of late mortality. This study aimed to evaluate malignancy frequency, mortality, and associated factors in a single-center IIM cohort. Methods: In this retrospective cohort study, all patients diagnosed with IIM and followed at Pamukkale University Faculty of Medicine between 2010 and 2025 were analyzed. Mortality rates, malignancy prevalence, and potential demographic and clinical determinants were assessed. Multivariable logistic regression analyses were performed, and results were reported as odds ratios with 95% confidence intervals. A two-sided P-value